2018
DOI: 10.3904/kjim.2018.197
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of bioimpedance analysis for assessing volume status in patients receiving maintenance dialysis

Abstract: Chronic volume overload is associated with left ventricular hypertrophy and high cardiovascular mortality in patients undergoing dialysis. Therefore, estimating body fluid status is important in these patients. However, most dry-weight assessments are still performed clinically, while attempts have been made to measure the volume status and dry weight of patients undergoing dialysis using bioimpedance analysis (BIA). BIA uses the electrical properties of the human body to alternate current flow and measures re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 66 publications
0
35
2
2
Order By: Relevance
“…It has been revealed that BIA is a useful, easily applicable, and inexpensive tool for the evaluation of body composition of obese [10], cardiometabolic disorders [1][2][3][4], cancer [8], and hemodialysis patients [18]. Obtaining confidential information with regarding specific proportion of each section of body composition (TBW, FFM, %FM and FM) in health and also some disorder is a continue interest of clinical and scientist.…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that BIA is a useful, easily applicable, and inexpensive tool for the evaluation of body composition of obese [10], cardiometabolic disorders [1][2][3][4], cancer [8], and hemodialysis patients [18]. Obtaining confidential information with regarding specific proportion of each section of body composition (TBW, FFM, %FM and FM) in health and also some disorder is a continue interest of clinical and scientist.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, for ICU patients, in whom fluid overload is common and has prevented BIA measurements from becoming a standard of practice. However, we circumvented this problem by using a multi-frequency BIA device (InBody S10), to enable differentiation between various fluid compartments [28,49,50], adjustment for the time from hospital admission to measurement, and recalculation of body composition to dry weight to reduce the effect of overestimating LBM by fluid overload. We recognize that under ideal circumstances, serial BIA measurements provide more details on the course of loss of muscle mass and fluid overload in critically ill patients.…”
Section: Limitations and Considerationsmentioning
confidence: 99%
“…However, methods to calculate dry body weight values have been described for dialysis patients, where fluid overload is prevalent [ 25 , 26 ]. The ratio between extracellular and total body water, as an indicator of hydration status, is easy to use, intuitive and validated as a predictor of survival in these patients [ 27 , 28 ]. This provides a theoretical justification to apply this technique to ICU patients.…”
Section: Introductionmentioning
confidence: 99%
“…BIA has been applied for the water management of hemodialysis patients and also recently for the water management of heart failure and cardiac surgery patients [16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…According to several reports on BIA in clinical studies, the phase angle (PA), one type of BIA readout, shared a correlation with a nutrition marker and was a potential postoperative risk marker for cardiac surgery [12][13][14][15]. Studies on the differences in water behavior with some kinds of diuretics found that one readout of BIA, the edema index (EI), being the ratio of extracellular water to total body water, can predict the amount of fluid reduction needed for patients with acute heart failure and chronic renal disease [16][17][18][19][20][21][22]. We hypothesized that perioperative water management could be improved by a better understanding of perioperative water behavior through BIA.…”
Section: Introductionmentioning
confidence: 99%